2020
DOI: 10.1016/j.jcot.2020.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of trauma and orthopaedic surgery at a UK District General Hospital during the Covid-19 pandemic

Abstract: Introduction: There are suggestions that elective surgery performed during the incubation period of COVID-19 infection may cause an immediate impairment of cell-mediated immunity, leading to high morbidity and mortality. However is contrasting data about the associated mortality. Since the outbreak, our unit has maintained a prospective database recording Trauma and Orthopaedic surgical activity. Our aim was to share our experience of the first 3 months with prospective data on outcome of essential surgery dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 19 publications
2
56
0
1
Order By: Relevance
“…29,591patients were studied during the COVID-19 pandemic, with reported ages ranging from under one to 103 years. The mean age was reported for 3,236 patients and was 43.7 years 13,18,19,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . An average of 54.8% were male.…”
Section: Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,591patients were studied during the COVID-19 pandemic, with reported ages ranging from under one to 103 years. The mean age was reported for 3,236 patients and was 43.7 years 13,18,19,22,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] . An average of 54.8% were male.…”
Section: Patient Demographicsmentioning
confidence: 99%
“…33 patients were COVID-19 positive on their first presentation, and 10 acquired COVID-19 after admission to hospital. The reported prevalence of COVID-19 in trauma patients ranged from zero in a District General Hospital in the UK 18 to 5.68% over multiple hospitals in Belgium 16 . 3 studies reported on mortality in nonproximal femur trauma patients; Sobti et al 18 reported that none of their patients died,…”
Section: Covid-19 Positive Trauma Patientsmentioning
confidence: 99%
“…Evidence revealed that mortality of patients hospitalized with COVID-19 was very high which is strongly associated with the presence of comorbidities, smoking, and substance use [23,25,34,39,45,51,52].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence revealed that mortality of patients hospitalized with COVID-19 was very high which is strongly associated with the presence of comorbidities, smoking, and substance use [23,25,34,39,46,[52][53][54].…”
mentioning
confidence: 99%